Magang Dasar Bidang Profesi Kependidikan - Jon A. Lalang Yame; Welhelmina Rahayu Laumalay; Selfince A. Atamau; Tuwentisri N. Maukay; Stevani Belplay (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Internship program activities are activities that provide initial experience to educators to become teachers who have pedagogical, personality, social and professional competencies which are also expected to develop creativity in apprentice participants in the educational professional field. This internship activity aims to directly observe school culture, observe basic, pedagogical, personality and social competencies, strengthen elementary level participants' understanding of the teaching and learning process directly in the classroom and reflect on the results of observations of the learning process. The method used in this report is descriptive qualitative direct observation in the field.